THE IMPLEMENTATION OF SURAKARTA REGIONAL REGULATION NUMBER 2 YEAR 2008 ABOUT DISABILITY EQULITY OF TRANSPORTATION FACILITY ACCESSIBILITY - Arifah, Kuni Nasihatun (Tadulako University, 2017)
The fulfillment of Human Rights is one of the indicators of a Legal State, Indonesia as a State of law mandated in the body of the 1945 Constitution of the State's obligation to fulfill human rights for every citizen of his country without exception including to the disabled, disabled is one of the citizens who are prone to discrimination. Perda Kota Surakarta No.2 Year 2008 about disability equality regulates the rights and obligations of the disabled and the obligation of government in realizing equality of disability including physical accessibility in public transportation and public service. In order to implement the regulation, regulation can be implemented. The form of impelemntasi aksebilitas public transportation facilities in Surakarta is with the BST (Bus Trans Surakarta) , halte bus and bus Begawan Abiyasa. AfterÂ implementation is run, there is an effort to increase Accessibility that is with the supervision of local regulations, the construction of tirtonadi terminal, and coordination.Hambatan that the Government in the effort to fulfill the right of accessibility Public transportation is a matter of funds and coordination between agencies.The result of the research shows that the implementation of the rights ofÂ Perda No.2 of 2008 on disability equality in Surakarta through three processes namely socialization, coordination and implementation and supervision and assessment, all of which have been running well but still require a lot of improvement especially in terms of coordination of implementation.